Productivity of Indigofera sp. at different drought stress level and defoliations interval - Herdiawan, Iwan; Sutedi, E (Indonesian Journal of Animal and Veterinary Sciences, 2012)
This study was aimed at determining the interaction between drought stress and defoliation interval on the productivity of Indigofera sp. This study was done based on Complete Randomized Design (CRD) 3x2 factorial, the first factor was without drought stress (100% FC), medium drought stress (50% FC), and severe drought stress (25% FC), and the second factor was the defoliation interval of 60 day and 90 days, each treatment was repeated 5 times. Observed variables were biomass production, and leaf/stem ratio. Results showed that there were significant interactions (P < 0.05) between drought stress and defoliations interval on the productivity of Indigofera sp. The highest biomass production of Indigofera sp. (424.47 g/plant) was obtained from treatment of wihtout dought stress (100% FC) combined with defoliations interval of 90 days, while the lowest (184.55 g/plant) was reached at treatment of severe drought stress (25% FC) and depoliations interval of 60 days. The highest leaf/stem ratio (1.47) was reahced at treatment severe drouht stress (25% FC) and depoliations interval of 60 days and the lowest (1.05) was reached at combination treatment of drought stress and depoliations interval of 90 days. Defoliations interval of 90 days showed higer biomass production than depoliations interval of 60 days. Key Word: Drought Stress, Depoliation, Indigofera sp